Gallbladder stones in bariatrics and management of choledocholithiasis after gastric bypass - Mariano Palermo; Manoel Galvao Neto (International Journal of Gastrointestinal Intervention, 2019)
It is known that the rapid weight loss is a predisposing factor to develop biliary lithiasis. The physiopathology is related with an oversaturation of bile with cholesterol, bile stasis, and increase in mucin concentration in bile. The incidence of cholelithiasis post gastric bypass is estimated around 37%. Almost 50% developed disease in the first year of monitoring, and 60% in the first 6 months. Meanwhile the patients undergoing sleeve gastrectomy have an incidence of cholelithiasis of 27%. Diverse kinds of protocols exist: prophylactic surgery (simultaneous cholecystectomy and gastric bypass in every patients, whether they have or not cholelithiasis), elective (simultaneous cholecystectomy with conventional gastric bypass in the patients with asymptomatic cholelithiasis), and conventional cholecystectomy only in the presence of cholelithiasis with symptoms. Which way to go is still a topic of discussion among surgeons but the majority agree that prophylactic surgery shouldn’t be an option because the number of patients that will develop symptomatic cholelithiasis is low (around 6% to 8% of them) and this leads to an elevated number of patients exposed to an unnecessary procedure with potential complications. The presence of gallstones in the common bile duct (CBD) although is a rare complication after Roux-en-Y gastric bypass (around 0.2% of the bariatric patients) represents an important challenge due to the anatomical modifications of the gastrointestinal tract. This leads to having to pursue other methods to reach the papillae for the resolution of choledocholithiasis: laparoscopy-assisted transgastric endoscopic retrograde cholangiopancreatography (ERCP), balloon enteroscopy assisted ERCP, percutaneous biliary drainage with subsequent trans fistula treatment and laparoscopic exploration of CBD. Which of these methods should we choose must be based on the surgeon experience, the equipment available and the location of the stone. But whatever the method, a special training is needed on endoscopy, percutaneous surgery and laparoscopy.